2016
DOI: 10.4111/icu.2016.57.6.424
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide incidence and treatment pattern of benign prostatic hyperplasia in Korea

Abstract: PurposeTo investigate the incidence of benign prostatic hyperplasia (BPH) in Korea and treatment patterns for 3 years after the diagnosis in a nationwide database.Materials and MethodsWe created a cohort of patients diagnosed of BPH between 2007 and 2011 from the Health Insurance Review & Assessment database, a nationwide database of reimbursement. The diagnosis of BPH was defined as having the diagnosis of BPH (N40.0 in International Classification of Diseases, 10th revision) as a primary or secondary diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
(33 reference statements)
0
35
1
Order By: Relevance
“…The incidence rate of urological diseases is increasing, especially in middle-aged men, and the prevalence of such diseases increases with age; an estimated 50% of men exhibit histologic evidence of benign prostatic hyperplasia (BPH) by age 50, increasing to 80% at age 80 [ 6 7 ]. BPH is a complex urinary disease that results in abnormalities due to prostate enlargement, which causes obstruction of the bladder and lower urinary tract [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of urological diseases is increasing, especially in middle-aged men, and the prevalence of such diseases increases with age; an estimated 50% of men exhibit histologic evidence of benign prostatic hyperplasia (BPH) by age 50, increasing to 80% at age 80 [ 6 7 ]. BPH is a complex urinary disease that results in abnormalities due to prostate enlargement, which causes obstruction of the bladder and lower urinary tract [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…BPH is a complex urinary disease that results in abnormalities due to prostate enlargement, which causes obstruction of the bladder and lower urinary tract [ 8 ]. Obstruction of urination normally leads to symptoms such as urinary frequency, urination disorder, and bladder occlusion, which may be symptomatic or asymptomatic depending on the patient [ 6 7 8 ]. Although the mechanism underlying BPH pathogenesis has not been fully elucidated, the most prevalent theory is that testosterone and dihydrotestosterone (DHT) are involved in the proliferation of prostate cells.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Regarding BHP, it is also a disease of men of older age group with mean age group above 50 years as revealed by previous studies. [24,25] In present study, the mean age for BHP is 62.79 (±8.67) and statistically it is not helpful to differentiate with prostate cancer (Table-1).…”
Section: Discussionmentioning
confidence: 55%
“…1 This condition triggers pressure on the urethra causing bladder outflow obstruction, and hence a variability of lower urinary tract symptoms (LUTS). 5,6 In order to reduce the complexities of BPH, innovative treatments developed in clinical practice have been widely employed with various efficacy and safety profiles. 4 It is also reported that BPH increases with age and affect more than 70% of elderly males.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is also reported that BPH increases with age and affect more than 70% of elderly males. 5,6 In order to reduce the complexities of BPH, innovative treatments developed in clinical practice have been widely employed with various efficacy and safety profiles.…”
Section: Introductionmentioning
confidence: 99%